Localized skin mottling associated with acute gastric dilatation. Issue 1 (16th January 2023) - Tominaga, Yoshiteru; Hirayama, Ichiro; Yano, Tetsuhiro; Kurihara, Kazuto; Ishii, Mitsuru
Abstract: We present a case of a 55‐year‐old woman complaining of abdominal distension owing to acute gastric dilatation. Her localized skin mottling had spread from the lower abdomen to both knees. The skin mottling in the area affected by gastric dilatation improved immediately after stomach emptying using a gastric tube and upper endoscopy. Abstract : As a complication with acute gastric dilatation, localized skin mottling disappeared immediately is a rare finding. Gastric dilatation could have caused compression of the inferior epigastric artery.